2022
DOI: 10.21203/rs.3.rs-1234293/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Classification of  Intracranial Hemorrhage  CT images for Stroke Analysis with Transformed and Image-based GLCM  Features

Abstract: Intracranial hemorrhage (ICH) is one of the severe types of brain stroke. Artery burst results in bleeding inside the brain and its surrounding tissue. Depending upon brain bleed location, hemorrhage gets classified. This paper presents a hybrid feature selection approach to form joint feature vector sets using transformed image features and image-based gray level co-occurrence matrix (GLCM) texture features. Feature extraction is performed by applying discrete wavelet transform, discrete cosine transform, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 3 publications
(3 reference statements)
0
5
0
Order By: Relevance
“…In [18], a hybrid feature selection approach uses transformed CT image features and grayscale co-occurrence matrix texture features. Features are extracted using discrete wavelet transforms, discrete cosine curves, and GLCMs.…”
Section: Main Types Of Strokementioning
confidence: 99%
“…In [18], a hybrid feature selection approach uses transformed CT image features and grayscale co-occurrence matrix texture features. Features are extracted using discrete wavelet transforms, discrete cosine curves, and GLCMs.…”
Section: Main Types Of Strokementioning
confidence: 99%
“…Moreover, the U-Net model achieved a 60% score, effectively discerning discrepancies between ischemic and hemorrhagic strokes [8]. Gudadhe and Thakare [9] developed a hybrid feature selection approach to extract a common feature vector from CT images by applying discrete wavelet transforms (DWT), discrete cosine transforms (DCT), and gray-level co-occurrence matrixes (GLCM) in a CT image. The CT images of intracranial hemorrhage are then classified by running random tree, random forest, and REP-Tree machine learning algorithms.…”
Section: Introductionmentioning
confidence: 99%
“…The CT images of intracranial hemorrhage are then classified by running random tree, random forest, and REP-Tree machine learning algorithms. The classification results showed that the highest accuracy was for the random forest classifier, which reached 87.97% for the DWT and GLCM feature sets [9]. The novelty of this work lies in using Orange3 as a new data mining method to extract a huge number of efficient features from CT images of patients with cerebral hemorrhage and employing these features in the cerebral hemorrhage classification process by applying four classification algorithms: logistic regression (LR), convolutional neural networks (CNN), support vector machine (SVM), and k-nearest neighbor algorithm (KNN).…”
Section: Introductionmentioning
confidence: 99%
“…25 Santwana and Anuradha proposed a hybrid feature group technique using discrete wavelet transform and image-based gray-level cooccurrence matrix (GLCM) that achieves 87.89% classification accuracy for a random forest classifier. 26 Pérez Del Barrio et al proposed a novel hybrid architecture based on image input from a 3D CNN and a feed-forward network for clinical data input. The model final component combines the outputs of the feed-forward and convolutional blocks and feeds this hybrid input to the final dense and activation layers to detect the presence of ICH.…”
Section: Introductionmentioning
confidence: 99%
“…On the collected dataset, the author performed validation by comparing the results of his proposed model with existing architectures, such as MobileNetV2 and VGG16 25 . Santwana and Anuradha proposed a hybrid feature group technique using discrete wavelet transform and image‐based gray‐level co‐occurrence matrix (GLCM) that achieves 87.89% classification accuracy for a random forest classifier 26 . Pérez Del Barrio et al proposed a novel hybrid architecture based on image input from a 3D CNN and a feed‐forward network for clinical data input.…”
Section: Introductionmentioning
confidence: 99%